ANTIBIOTICS SUSCEPTIBILITY PATTERNS OF BACTERIAL ISOLATES FROM UNPASTEURIZED MILK SOLD AT KADUNA STATE UNIVERSITY (FUDMA JOURNAL OF SCIENCES, 2023)
A total number of twenty four (24) random samples of unpasteurized milk were collected from three different locations in Kaduna State University, main campus to assess their microbiological quality and determine the antibiotics susceptibility patterns of the bacteria isolates. Total viable bacteria and coliform counts were carried out using pour plate method. Antibiotics susceptibility test was carried out using Kirby Bauer modified disc diffusion method, while multiple antibiotic resistance (MAR) index of isolates were also determined using recommended procedure. Results obtained revealed that the mean values of total viable bacterial counts ranged from 1.1 x 105 to 2.1 x 105 cfu/ml. Total coliform counts was from 4.6x104 to 7.8x105 cfu/ml. Six different bacteria were isolated from the samples, they were: Bacillus spp (18.8%), E. coli (18.8%), Lactobacillus spp (6.25%), Proteus vulgaris (18.8%), Staphylococcus. aureus (25.0%), and Streptococcus spp (12.5%). Antibiotic susceptibility test of the isolated organisms showed that Gram negative isolates were more resistant to antibiotic action than Gram positive isolates, 18.8% of Gram positive isolates and 75% of Gram negative isolates had MAR index greater than 0.2. The findings of this study showed that the unpasteurized milk samples were contaminated with bacteria including faecal contaminants and that these isolates may have originated from a high risk source of contamination where antibiotics are often used
Keywords: antibiotics susceptibility, contaminants, unpasteurized milk